Strategic Delegation under Cost Asymmetry - Flavio Delbono; Luca Lambertini; Luigi Marattin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
We revisit the two-stage duopoly game with strategic delegation and asymmetric technologies of Sen and Stamatopoulos (2015). We show that their conclusions are misled by the restrictive assumption that the extent of delegation to managers is restricted to a binary set. Allowing for a continuous set of delegation incentives, we prove that the delegation stage is a prisoners dilemma, the unique subgame perfect equilibrium entailing both firms hiring managers. At equilibrium, the more efficient firm makes higher profits.
Keywords: D43; L13; 330